Does the High Nucleic Acid Content of Individual Bacterial Cells Allow Us To Discriminate between Active Cells and Inactive Cells in Aquatic Systems? - Lebaron, Philippe (American Society for Microbiology, 2001)
The nucleic acid contents of individual bacterial cells as determined with three different nucleic acid-specific fluorescent dyes (SYBR I, SYBR II, and SYTO 13) and flow cytometry were compared for different seawater samples. Similar fluorescence patterns were observed, and bacteria with high apparent nucleic acid contents (HNA) could be discriminated from bacteria with low nucleic acid contents (LNA). The best discrimination between HNA and LNA cells was found when cells were stained with SYBR II. Bacteria in different water samples collected from seven freshwater, brackish water, and seawater ecosystems were prelabeled with tritiated leucine and then stained with SYBR II. After labeling and staining, HNA, LNA, and total cells were sorted by flow cytometry, and the specific activity of each cellular category was determined from leucine incorporation rates. The HNA cells were responsible for most of the total bacterial production, and the specific activities of cells in the HNA population varied between samples by a factor of seven. We suggest that nucleic acid content alone can be a better indicator of the fraction of growing cells than total counts and that this approach should be combined with other fluorescent physiological probes to improve detection of the most active cells in aquatic systems.